The Influence of Unevenly Distributed Powder on a 1000 MW Opposed Firing Boiler and the Counter Measures - Ming GE; Zhicheng JIANG; Zhijia LV; Jiayang WANG; Zhaohong QIU; Shouyu ZHANG (Zhongguo dianli)
An experimental study was carried out on deviant combustion of a 1000 MW opposed firing boiler. It was found that the powder deviation is the main factor. The distributions of powder amount and pulverized coal fineness demonstrated a typical interval distribution trend as well as a positive correlation. The factors such as uneven distribution of powder amount, deviation of pulverized coal fineness and air distribution characteristics of secondary-air-box led to the deviant combustion in the furnace. In order to alleviate the deviant combustion in the furnace, the fineness of pulverized coal, the air distribution of the burner, the swing angle of the burning wind, and the opening of closing-to-wall air were adjusted. It was found that the adjustment of burning wind opening and swing angle have the most significant influence. The decrease of burning wind opening and the swing angle of burning wind from the middle to both sides were helpful to alleviate the deviant combustion. After adjustment, the deviation of steam temperature at screen superheater outlet was reduced from 40 ℃ to less than 10 ℃. Under the full load condition, the lowest point of oxygen concentration at the outlet of the economizer was increased from less than 1% to more than 2%. The highest point of CO concentration decreased from more than 5000 μL/L to less than 500 μL/L. The deviant combustion was greatly alleviated. The combustion adjustment could provide reference for the same type of units to solve the problem of deviant combustion.